2015
DOI: 10.1002/mus.24600
|View full text |Cite
|
Sign up to set email alerts
|

Orthoptic and video‐oculographic analyses in oculopharyngeal muscular dystrophy

Abstract: The data indicate preferential involvement of lateral and (to a lesser degree) superior rectus muscles in OPMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…We confirm these findings with similar frequencies of involved EOM, although variability between patients remains high. In CPEO and OPMD, the SR appears to be the most predominantly involved muscle, in line with results from previous studies 35–37…”
Section: Discussionsupporting
confidence: 91%
“…We confirm these findings with similar frequencies of involved EOM, although variability between patients remains high. In CPEO and OPMD, the SR appears to be the most predominantly involved muscle, in line with results from previous studies 35–37…”
Section: Discussionsupporting
confidence: 91%
“…If any of the prescreening questions were answered positively and any of the vision screening shapes were not correctly identified, then the participant was excluded from the study (n = 3). Participants were excluded from the study if they reported any of the following conditions, which may have prevented successful test calibration during the prescreening process: this included vision-related issues such as extreme tropias, phorias, static visual acuity of >20/400, nystagmus, cataracts or eyelash impediments or if they had consumed drugs or alcohol within 24 h of testing (n = 1) (Han et al, 2010;Holmqvist and Nystrom, 2011;Renard et al, 2015;Kooiker et al, 2016;Niehorster et al, 2017). Participants were also excluded if they were unable to pass a nine-point calibration sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were excluded from participation in the study if they met any of the following prescreening conditions: neurological disorders (such as concussion, traumatic brain injury, Parkinson's disease, Huntington's disease, cerebral palsy); obvious vision-related issues that prevented successful calibration 24,25 of all nine points (such as extreme tropias, 26 phorias, 26,27 static visual acuity of greater than 20/400, 24 nystagmus, 24,28 cataracts, 29 or eyelash impediments 29 ); small vessel strokes; or consumption of drugs or alcohol within 24 hours of testing. Participants removed any eyewear, including glasses or contact lenses.…”
Section: Methodsmentioning
confidence: 99%